2009
DOI: 10.1007/s11103-009-9589-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of auxin signaling mediated by IAA14 and ARF7/19 in membrane lipid remodeling during phosphate starvation

Abstract: In higher plants, phosphate (Pi) deficiency induces the replacement of phospholipids with the nonphosphorous glycolipids digalactosyldiacylglycerol (DGDG) and sulfoquinovosyldiacylglycerol (SQDG). Genes involved in membrane lipid remodeling are coactivated in response to Pi starvation, but the mechanisms that guide this response are largely unknown. Previously, we reported the importance of auxin transport for DGDG accumulation during Pi starvation. To understand the role of auxin signaling in Arabidopsis memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 53 publications
(105 reference statements)
1
37
0
Order By: Relevance
“…In a previous report, we have shown that galactolipids accumulate in the root of slr-1 mutants without upregulation of MGD2 , MGD3 , DGD1 , and DGD2 under nutrient-sufficient conditions (Narise et al, 2010). Furthermore, MGD1 expression in the slr-1 root remained at the same level as in the wild-type plants ( Figure 5A ), indicating that the increase in galactolipids in the slr-1 roots was not due to the transcriptional activation of the galactolipid synthesis genes.…”
Section: Discussionmentioning
confidence: 90%
“…In a previous report, we have shown that galactolipids accumulate in the root of slr-1 mutants without upregulation of MGD2 , MGD3 , DGD1 , and DGD2 under nutrient-sufficient conditions (Narise et al, 2010). Furthermore, MGD1 expression in the slr-1 root remained at the same level as in the wild-type plants ( Figure 5A ), indicating that the increase in galactolipids in the slr-1 roots was not due to the transcriptional activation of the galactolipid synthesis genes.…”
Section: Discussionmentioning
confidence: 90%
“…flu1 plants accumulate protochlorophyllide, an intermediate in the chlorophyll biosynthesis pathway and release singlet oxygen in plastids upon a dark/light shift (Laloi et al, 2006). arf7arf19 is a loss-of-function mutant of the auxin response factors ARF7 and ARF19 (Narise et al, 2010). Therefore, the genes of cluster B, while responding to SA, appear to be less characteristic of a typical SA response, and might correspond to a more general stress response like the oxidative stress response.…”
Section: Resultsmentioning
confidence: 99%
“…In shoots of WT plants, the molar ratio of DGDG in the total membrane lipids was increased when sucrose was supplemented, whereas that of MGDG was decreased (Figure 5A). Although the level of MGD3 mRNA in OE7 under sucrose supplementation was markedly higher than that observed in WT plants grown under Pi depletion (Figure 3A; Narise et al, 2010), only a small increase in DGDG mol% was observed in OE7 shoots compared with WT shoots (Figure 5A). Thus, we also analyzed lipid composition of the microsomal fraction extracted from shoots of WT and OE7 supplemented with sucrose (Figure 5B).…”
Section: Resultsmentioning
confidence: 85%
“…Although NPC5 , DGD1 , and DGD2 are responsive to Pi starvation and are involved in membrane lipid remodeling under Pi depletion (Härtel et al, 2000; Kelly and Dörmann, 2002; Kelly et al, 2003; Gaude et al, 2008), their expression in shoots was not significantly affected by sucrose supplementation (Figure 1A). IPS1 and At4 are non-protein-coding genes that are strongly and specifically induced by Pi starvation but are not related to lipid synthesis (Martín et al, 2000; Rubio et al, 2001; Bari et al, 2006; Narise et al, 2010). Expression of both IPS1 and At4 in shoots was increased by sucrose supplementation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation